2015
DOI: 10.1038/srep11150
|View full text |Cite
|
Sign up to set email alerts
|

A zero density change phase change memory material: GeTe-O structural characteristics upon crystallisation

Abstract: Oxygen-doped germanium telluride phase change materials are proposed for high temperature applications. Up to 8 at.% oxygen is readily incorporated into GeTe, causing an increased crystallisation temperature and activation energy. The rhombohedral structure of the GeTe crystal is preserved in the oxygen doped films. For higher oxygen concentrations the material is found to phase separate into GeO2 and TeO2, which inhibits the technologically useful abrupt change in properties. Increasing the oxygen content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 43 publications
6
43
0
Order By: Relevance
“…Extensive works have been done to explore the effects of oxygen or nitrogen on the properties of phase change material Ge 2 Sb 2 Te 5 (GST) and GeTe. [19][20][21][22][23][24][25] Some general conclusions have been made including that oxygen/nitrogen will modify the local structure of amorphous GST/GeTe due to the strong Ge-O/Ge-N bonding. Most importantly, the doping effects are about the crystallization kinetics, for example, it is found that N can slow down the crystal growth of GST, [26][27][28] which will improve the data-retention property of the amorphous GST.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive works have been done to explore the effects of oxygen or nitrogen on the properties of phase change material Ge 2 Sb 2 Te 5 (GST) and GeTe. [19][20][21][22][23][24][25] Some general conclusions have been made including that oxygen/nitrogen will modify the local structure of amorphous GST/GeTe due to the strong Ge-O/Ge-N bonding. Most importantly, the doping effects are about the crystallization kinetics, for example, it is found that N can slow down the crystal growth of GST, [26][27][28] which will improve the data-retention property of the amorphous GST.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the doping effects are about the crystallization kinetics, for example, it is found that N can slow down the crystal growth of GST, [26][27][28] which will improve the data-retention property of the amorphous GST. While for GeTe, oxygen was reported to increase its crystallization temperature, 21 thus enabling the application of GeTe at higher temperature. More recently, further experimental study 20 showed that oxygen can also increase the resistivity of GeTe, resulting in a substantial reduction of switching voltage for the devices based on GeTe-O films.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between T tr and the critical temperature, T c , is a measure of how far the transition is from being thermodynamically continuous and, although this should include the saturation temperature from Equation A.5, it is usually adequate to ignore it in fitting data above room temperature. Figures A.1b and A.1c show fits of a function of the form of Equation A.12 to data for e 4 and e a derived from the lattice parameters of Levin et al [7], Chatterji et al [16] and Hudspeth et al [15]. T tr was fixed at the experimental values and the resulting fit parameters are listed in Table A.II.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…GeTe is a remarkable material in several topical contexts, including as an end-member phase for crystal-to-amorphous phase change memory [1][2][3][4], for nanowire memory devices [5], as a base for thermoelectric materials [6.7] and as a ferroelectric at room temperature which retains "a reversible, size dependent polar-nonpolar transition in nanocrystal ensembles" [8]. Close interest arises because of the particular combination of structure and electronic properties which can give fast switching and stable storage.…”
Section: Introductionmentioning
confidence: 99%
“…In the same work, it was also observed that the PCM crystallization depends not only on the magnitude but also on the duration of applied current pulse [7]. However, poor thermal stability in amorphous phase GST and void formation due to volume shrinkage upon crystallization limit the GST application range [8]. In comparison to GST, GeTe has several advantages including higher stability in amorphous phase, ultra-fast reversible phase transition (µs-to crystallize and ns-to amorphized), and higher OFF/ON resistivity ratio.…”
Section: Introductionmentioning
confidence: 68%